Hierarchical α-MnO 2 nanowires@Ni1-xMnxOy nanoflakes core-shell nanostructures for supercapacitors - Lou, David Xiong Wen (2014)
A facile two-step solution-phase method has been developed for the preparation of hierarchical α-MnO2 nanowires@Ni1-xMnxOy nanoflakes core–shell nanostructures. Ultralong α-MnO2 nanowires were synthesized by a hydrothermal method in the first step. Subsequently, Ni1-xMnxOy nanoflakes were grown on α-MnO2 nanowires to form core–shell nanostructures using chemical bath deposition followed by thermal annealing. Both solution-phase methods can be easily scaled up for mass production. We have evaluated their application in supercapacitors. The ultralong one-dimensional (1D) α-MnO2 nanowires in hierarchical core–shell nanostructures offer a stable and efficient backbone for charge transport; while the two-dimensional (2D) Ni1-xMnxOy nanoflakes on α-MnO2 nanowires provide high accessible surface to ions in the electrolyte. These beneficial features enable the electrode with high capacitance and reliable stability. The capacitance of the core–shell α-MnO2@Ni1-xMnxOy nanostructures (x = 0.75) is as high as 657 F g−1 at a current density of 250 mA g−1, and stable charging-discharging cycling over 1000 times at a current density of 2000 mA g−1 has been realized.